Imaging of long head biceps tendon. A multimodality pictorial essay - Zappia, Marcello; Chianca, Vito; Di Pietto, Francesco; Reginelli, Alfonso; Natella, Raffaele; Maggialetti, Nicola; Albano, Domenico; Russo, Raffaele; Sconfienza, Luca Maria; Brunese, Luca; Faletti, Carlo (Acta Biomedica Atenei Parmensis, 2019)
The aim of this is article is to provide an  imaging review of normal anatomy, most common anatomical variants and pathologies of the long head of the biceps tendon (LHB) encountered during the daily practice.